2009
DOI: 10.1103/physreve.79.026703
|View full text |Cite
|
Sign up to set email alerts
|

Generalized lattice Boltzmann equation with forcing term for computation of wall-bounded turbulent flows

Abstract: In this paper, we present a framework based on the generalized lattice Boltzmann equation (GLBE) using multiple relaxation times with forcing term for eddy capturing simulation of wall-bounded turbulent flows. Due to its flexibility in using disparate relaxation times, the GLBE is well suited to maintaining numerical stability on coarser grids and in obtaining improved solution fidelity of near-wall turbulent fluctuations. The subgrid scale (SGS) turbulence effects are represented by the standard Smagorinsky e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 91 publications
1
84
0
Order By: Relevance
“…In addition, for the generalization of the split-forcing IB-LBM, we consider not only Guo et al's split-forcing LBE [35] but also Cheng and Li's split-forcing LBE [38]. The latter enables us to extend our direct-forcing IB-LBM based on split-forcing LBE with single-relaxation time (SRT) to generalized split-forcing LBE with multi-relaxation time (MRT) [39], which is important for the broad applications of the IB-LBM, especially for high-Reynolds flows, because the LBE with MRT can attain better stability than the LBE with SRT. In Section 2.2, we account for explicit and implicit diffuse and sharp interface schemes to be assessed in this study.…”
mentioning
confidence: 96%
“…In addition, for the generalization of the split-forcing IB-LBM, we consider not only Guo et al's split-forcing LBE [35] but also Cheng and Li's split-forcing LBE [38]. The latter enables us to extend our direct-forcing IB-LBM based on split-forcing LBE with single-relaxation time (SRT) to generalized split-forcing LBE with multi-relaxation time (MRT) [39], which is important for the broad applications of the IB-LBM, especially for high-Reynolds flows, because the LBE with MRT can attain better stability than the LBE with SRT. In Section 2.2, we account for explicit and implicit diffuse and sharp interface schemes to be assessed in this study.…”
mentioning
confidence: 96%
“…By carefully separating the relaxation times of hydrodynamic and non-hydrodynamic moments, it has been shown that the MRT-LBM significantly improves the numerical stability [17,18] and better physical representation in certain problems such as kinetic layers near boundaries [19], when compared with the SRT-LBM. Such MRT models have recently been shown to reproduce challenging fluid mechanics problems such as complex turbulent flows with good quantitative accuracy [20,21]. An important and natural simplification of the MRT model is the two-relaxation-time (TRT) model, in which the moments of even and odd orders are relaxed at different rates [22].…”
Section: Introductionmentioning
confidence: 99%
“…The change in distribution function due to collisions as a relaxation process and external forces is represented by ̟, and following Premnath et al [46] it can written as…”
Section: Generalized Lattice Boltzmann Equation With Forcing Termmentioning
confidence: 99%
“…density ρ and momentum − → j , are as follows [37]: The components of the source terms in moment space are functions of external force − → F and velocity fields − → u , and are given as follows [46]:…”
Section: A2 D3q19 Modelmentioning
confidence: 99%
See 1 more Smart Citation